Mock News: On the discourse of mocking in U.S. televised political discussions. Issue 1 (February 2022) - Jenks, Christopher
American televised political shows are under tremendous pressure to succeed within an economic model that requires maximizing viewership. In response to this growing financial pressure, political shows invite contentious guests to discuss current events and issues. Such discussions are often confrontational, making a mockery of the responsibility the news industry has in disseminating information in an impartial and insightful way. Although outrage is a common discourse feature of televised political shows, little is known about what this language looks like and how it is used to argue ideological positions. To this end, drawing from critical discourse analysis, this study investigates the multidimensional and multifunctional aspects of mocking, which is a type of outrage discourse. The findings show that mocking is an important argumentative tool for panel members, which occurs in the turn following an opposing viewpoint and is used to carry out a range of actions, including expressing disagreement, establishing a competing ideological position, and refuting an idea based on an opponent's political identity, to name a few. These findings contribute to a better understanding of how mocking and mock news feed into partisan ideologies, creating both tribalism and skepticism within society.